Who says women can't be doctors? : the story of Elizabeth Blackwell - Stone, Tanya Lee (Christy Ottaviano Books/Henry Holt and Co., 2013)
An introduction to the life and achievements of the first American female doctor describes the limited career prospects available to women in the early nineteenth-century, the opposition Blackwell faced while pursuing a medical education, and her pioneering medical career that opened doors for future generations of women.